2017
DOI: 10.1111/fare.12230
|View full text |Cite
|
Sign up to set email alerts
|

Scripting Sexual Consent: Internalized Traditional Sexual Scripts and Sexual Consent Expectancies Among College Students

Abstract: College students are at a relatively high risk for both sexual assault victimization and perpetration, and understanding sexual consent is imperative to reduce the incidence of sexual assault. Informed by the interactionist perspective of feminist theory, we surveyed 447 undergraduate students to identify factors associated with heterosexual college students' expectancies related to sexual consent. Women who believed in sexual stereotypes and endorsed music that degrades women were less likely than other women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Understanding consent is important as it helps distinguish between voluntary sexual contact and sexual assault. There are differing scholarly opinions and critiques of the construct (Croskery-Hewitt, 2015; Hust, Rodgers, & Bayly, 2017). Consent in itself is difficult to define with some scholars writing about consent without defining it (Scott & Graves, 2017).…”
Section: Stealthfully Violatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding consent is important as it helps distinguish between voluntary sexual contact and sexual assault. There are differing scholarly opinions and critiques of the construct (Croskery-Hewitt, 2015; Hust, Rodgers, & Bayly, 2017). Consent in itself is difficult to define with some scholars writing about consent without defining it (Scott & Graves, 2017).…”
Section: Stealthfully Violatedmentioning
confidence: 99%
“…It would seem like the issue around nonconsensual condom removal is not sufficiently addressed in the sexual consent literature. Muehlenhard et al (2016) and Hust et al (2017) report that the complexity of consent is embedded in gendered sexual scripts. Issues around consent in the Global North seem to differ to issues around consent in SSA.…”
Section: Stealthfully Violatedmentioning
confidence: 99%
“…In this way, it is not that these men do not know what is happening, but they are deliberate in their actions. As an example, one study found that men who reported committing sexual violence in the past were more likely to say that they did not expect to respect and adhere to their partner’s decision to engage in sex or not [ 151 ]. In addition, reporting an interest in the use of VSC to obtain sex was correlated with reports of past sexual aggression [ 67 ].…”
Section: Consentmentioning
confidence: 99%
“…Sexual script theory posits that meanings related to human sexuality can be conveyed through a variety of sources and at various levels, including at the cultural, interpersonal, and intrapsychic, or individual desire, level (Simon & Gagnon, 1986). Sexual scripts (e.g., ideas about how men and women should behave in certain sexual situations) to which people ascribe have been associated with increased sexual risk behaviors (Bowleg et al, 2015) and unhealthy sexual consent negotiation (Hust et al, 2017). For example, Bowleg et al (2015) developed a sexual scripts scale and examined associations between sexual scripts and risk behaviors among Black heterosexual men.…”
Section: Sex-related Marijuana Expectanciesmentioning
confidence: 99%